PROWADZENIE POLITYKI ZAGRANICZNEJ W RZECZYPOSPOLITEJ POLSKIEJ - Mażewski, Lech (Wydział Prawa i Administracji UAM, 2009)
The Constitution of 2 April 1997 explicitly grants the right to conduct Polish foreign policy to the Council of Ministers, although the role of President as well as the Seym and Senate in this sphere of state activity is also recognised. And indeed, in the present legal state, it is the government which is the main animator of Poland’s activity on the international scene, notwithstanding the fact that certain residual albeit important entitlements are vested in the Seym. They include deciding about the state of war and negotiations of peace, or participation, along with the Senate, in ratification processes of some (most important) international agreements. As far as the function of president is concerned, the legislator’s intention was to minimise that role, reducing it to the representative of the state in external relations, and taking co-lead in the foreign policy of the state. This solution, however, has failed to have been successfully implemented and nowadays it seems that the main domain of President as the chief of state is ratification of international agreements.
CONDUCTING FOREIGN POLICY IN THE REPUBLIC OF POLAND